Sunflower shell waste as an alternative animal feed - Nor Surayah, Osman; Norzahir, Sapawe; Muhammad Adhwa 'Uthaqif, Sapuan; Muhammad Farhan, Mohd Fozi; Muhd Haikal Iskandar, Fakhrul Azman; Adam Harith, Zafrul Fazry; Muhammad Zafri Haiqal, Zainudin; Muhammad Farhan, Hanafi (Elsevier Ltd., 2018)
Utilization of waste from food manufacturing processes in animal feed is not a novel concept. As one of the five oil crops second to bean and cotton, Helianthus annuus or sunflower. L has received more and more favour due to the good taste and superb medicinal effect of its seed. Higher demand in sunflower oil and other affiliated industry has generate an abundant source of sunflower shell. This study focuses on the conversion of sunflower shell as alternative animal feed. Initial study been performed on collected waste sunflower shell after its been prepared into powder. Chemical composition analysis demonstrates high percentage of lignin (50) and crude fibre (21), indicate that major constituent of sunflower shell is made up of carbohydrate. Other composition including water 6.5, lipid 5.17, amino acid 4 and ash 2.1. Biological analysis via viable plate count shown that number of microbes is too few too count. Toxicity analysis based on BSLA provide its chronic toxicity is 1g/ml which define that sunflower shell powder is low in toxicity. The formulation of sunflower shell has successfully converted this by-product into pellet that suitable for animal consumption